BEYOND THE SPOTLIGHT: UNSUNG HEROES OF THE INDIAN FREEDOM STRUGGLE (International Journal of Food and Nutritional Sciences, 2022)
An important turning point in Indian history was the country's struggle for independence. It is a series of historical occurrences and several liberations fighters’ self-immolations. The frequently underappreciated achievements of numerous unidentified heroes from Northeastern India who actively took part in the nation's freedom fight are highlighted in this study piece. The study emphasizes the sacrifices made by people like Tirupur Kumaran, Satyavati Devi, Kamaladevi Chattopadhyay, Khudiram Bose, Nirvair Singh, Karam Singh Kandola, and Gurdit Singh while also appreciating the well-documented efforts of notable characters. The essay highlights the necessity to honor and commemorate the wide diversity of people who fought for India's freedom through a survey of secondary sources, making sure their tales are not lost to history